2018
DOI: 10.1186/s13643-018-0838-y
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin complex concentrate versus placebo, no intervention, or other interventions in critically bleeding patients associated with oral anticoagulant administration: a protocol for a systematic review of randomised clinical trials with meta-analysis and trial sequential analysis

Abstract: BackgroundAcute critical bleeding is one of the most feared complications during treatment with oral anticoagulating agents. As more patients undergo treatment with anticoagulating agents, critically bleeding episodes in patients with vitamin K antagonists, thrombin inhibitor, or factor Xa inhibitor-inducted coagulopathy will be encountered frequently by physicians. Hence, an effective treatment capable of reversing the iatrogenic coagulopathy in the acute setting is needed. In randomised clinical trials and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…The area under the receiver operating characteristic curve of RFR for detection of AKI was 0.83 (95% confidence interval [CI] = 0.70 to 0.96); and using an RFR cutoff of 15 mL/min/1.73 m 2 has 67% sensitivity and 94% specificity for prediction of postoperative AKI. Patients with preoperative RFR ≤15 mL/min/1.73 m 2 were 11.8 times more likely to experience AKI than those who had RFR >15 mL/min/1.73 m 2 .…”
Section: Acute Kidney Injury After Cardiac Surgerymentioning
confidence: 92%
See 2 more Smart Citations
“…The area under the receiver operating characteristic curve of RFR for detection of AKI was 0.83 (95% confidence interval [CI] = 0.70 to 0.96); and using an RFR cutoff of 15 mL/min/1.73 m 2 has 67% sensitivity and 94% specificity for prediction of postoperative AKI. Patients with preoperative RFR ≤15 mL/min/1.73 m 2 were 11.8 times more likely to experience AKI than those who had RFR >15 mL/min/1.73 m 2 .…”
Section: Acute Kidney Injury After Cardiac Surgerymentioning
confidence: 92%
“…Until recently, the only options to reverse the effects of this drug class has been the administration of plasma or factor concentrates. 2 In May of 2018, the Food and Drug Administration (FDA) approved intravenous (IV) andexanet alfa (Andexxa, Portola Pharmaceuticals, San Francisco, CA), a first-in-class, recombinant, modified factor Xa protein, for the reversal of the anticoagulant effects of rivaroxaban and apixaban, in patients with life-threatening or uncontrolled bleeding. 3 Andexanet alfa acts as a decoy and binds to factor Xa inhibitors, thus neutralizing their anticoagulant effects.…”
Section: Reversal Of Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific Anticoagulation Reversal Fresh frozen plasma (FFP) has been widely used for many years, but its use is limited in routine practise by blood type matching, maximal acceptable or possible complications related to fluid overload, so its use has been supplanted by prothrombin complex concentrates (PCCs), particularly in situations involving critical bleeding (17,18). Four-factor PCC consists of vitamin Kdependent coagulation factors (II, VII, IX, and X) with a final overall clotting factor concentration that is approximately 25 times higher than in normal plasma (19).…”
Section: Reversion Of Anticoagulant Activity: What Are We Talking About?mentioning
confidence: 99%
“…Four-factor PCC consists of vitamin K-dependent coagulation factors (II, VII, IX, and X) with a final overall clotting factor concentration that is approximately 25 times higher than in normal plasma ( 19 ). Several studies have shown that PCCs act more quickly and effectively than FFP in terms of correcting the INR of patients on VKA ( 16 , 18 ). The effect of PCC on NOAC-associated ICH is less clear.…”
Section: Reversion Of Anticoagulant Activity: What Are We Talking About?mentioning
confidence: 99%